Improving perinatal health: Are Indian health policies progressing in the right direction? - Sharad K Singh; Ravinder Kaur; P K Prabhakar; Madhu Gupta; Rajesh Kumar (Wolters Kluwer Medknow Publications, 2017)
Background: Strategic investments and policy directives of the Indian Government has demonstrated highest degree of political commitment for maternal and child health care. Objectives: To evaluate the impact of the rise in institutional deliveries in India on perinatal mortality. Methods: Hospital delivery rate and perinatal mortality rate (PNMR), reported by Sample Registration System, Registrar General of India, on a representative sample was used. The correlation between relative change in hospital deliveries and PNMR was examined. Results: In rural areas of India, hospital deliveries have increased during 2005-2013 from 24.4 to 69.7% and PNMR has declined from 40 to 28 per 1000 births. At the state level, there was significant correlation between the rise in hospital delivery rate and decline in PNMR (r 0.4, p 0.04). Conclusions: Decline in perinatal rates can be attributed to India's strategic initiatives in health policy and planning for increasing deliveries in hospitals.